STUDI ANALISIS SEKATAN SESAR PADA LAPANGAN BANTENG, CEKUNGAN SUMATRA TENGAH, RIAU - MELOZA , KAUSAR
Fault can act as a seal or migration path of trapped hydrocarbon in the reservoir. One of the factor which controls this sealing property of this fault is the fault zone permeability, which also is a function of capillary entry pressure so that it depends on the grain size of the fault zones constituent. The composition of the phyllosillicate that can be predicted through vshale calculation in the well log at fault zones thus can become the parameter in predicting the nature of the fault sealing property. Data which are used to this study are core data, Side Wall Core data (SWC), biostratigraphy data, 3D seismic data and pressure data which obtained from Repeat Formation Test (RFT). Methodology which is used to analyze the fault seal is Shale Gouge Ratio (SGR), which is one of the most robust methods used to predict fault sealing properties. This research area is dominated by N-S to NW-SE striking reverse fault indicating the geometry of positive flower structure, which is the characteristic of region affected by strike-slip regime. At the west side of this research area, there are reverse faults with relatively large throw, while at the middle to the east side of this area, there are faulted fold culmination with higher elevation. According to well and repeat formation test data, there are indications that fault seal in the research area is exist. Fault seal analysis on fault 4, 5 and 6 based on juxtaposition, SGR distribution map and repeated formation test suggest that with minimum SGR value of 20%, the indicated sealing fault at the area has been able to withstand 13.1 bar differential across-fault pressure. This conclusion should be noted as minimum because this fault and research area are in the strike-slip system.